Decoding Patriarchy and Female Identity The Misrepresentation of Rosie in "The Guide" - Rahman, Md.Naimur; Talukder, Md. Jobaar (Language, Technology, and Social Media, 2025)
This study reinterprets the character of Rosie in R.K. Narayan’s The Guide through a feminist lens, addressing how patriarchal values shape her misrepresentation and the tendency to blame her for Raju’s downfall. In Indian society, women’s identities are often overshadowed by restrictive cultural norms, and female agency is frequently misconstrued as self-serving or morally flawed. This study critically examines Rosie’s role within the novel, challenging traditional readings that view her as an opportunist rather than a woman asserting her independence within an oppressive environment. Utilizing a mixed-method approach, this study combines qualitative textual analysis with survey data gathered from university scholars to assess public perceptions of Rosie’s character. This dual approach reveals how deeply ingrained patriarchal ideologies shape cultural and literary judgments, often clouding objective assessments of female agency. Results indicate that many readers still interpret Rosie’s actions through a lens tainted by cultural bias, reflecting a broader societal reluctance to accept independent women who break from prescribed roles. By emphasizing a more balanced understanding, this study advocates for interpretations that appreciate the complexity of female characters and recognize their agency within literature shaped by patriarchal contexts. Contributing to the field of feminist literary criticism, this study underscores the need for inclusive and informed perspectives that challenge entrenched gender biases. Ultimately, this study provides a critical framework for future research on gender representation in literature, encouraging scholars to question cultural assumptions and explore how literary interpretations can evolve to promote gender equity in global narratives.